SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KUALITAS TELUR PADA AYAM PETELUR MENGGUNAKAN METODE AHP - Muslim Alamasyah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Chicken eggs are a lot of animals for human consumption, and chickens are part of livestock dirizkikan by Allah  as contained in the phrase "sustenance which God has beengiven to  them in the form of cattle "contained in the letter of Al-Hajj verse 28. Therefore,not a few people then are interested in developing a poultry farm. Maintenance of layinghens require special handling and are very important for diperhatian. Due to the goodmaintenance will result in the growth of good chicken, the chicken is a healthy, lowmortality rate and will ultimately result in laying hens with good quality eggs. Developingfarms require a large influential technology system for the quality of the chicken egg asDecision Support System for Determining the Quality of Laying hens eggs using AHPmethod. Analytical Hierarchy Process (AHP) is a theory of measurement that is used tofind the scale ratio by performing pairwise comparisons between factors. This studyfocused on How to design and create applications decision support system that can be usedto determine the quality  eggs in laying hens. The results showed that, for a DecisionSupport System. Determining the quality of Laying Chicken eggs can be seen from severalfactors where each factor has a certain criteria with a specific value that is used as aparameter in egg quality of laying hens.